2018
DOI: 10.1111/wre.12342
|View full text |Cite
|
Sign up to set email alerts
|

A review of the relationship between primary and secondary dormancy, with reference to the volunteer crop weed oilseed rape (Brassica napus)

Abstract: Fresh seeds of oilseed rape (Brassica napus) are reported to be nondormant and nonphotoblastic. However, a portion of the seeds can be induced into a light-requiring state (secondary dormancy) for germination and also exhibit dormancy cycling. Thus, if seeds become buried in the soil they can form a persistent seedbank and become a serious volunteer weed in succeeding crops. The capacity of nondormant seeds of B. napus to be induced into secondary dormancy is contrary to results of studies on fresh nondormant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 57 publications
3
36
0
Order By: Relevance
“…Differences in competitive ability amongst surrogate weeds are expected due to differing growth rates, fecundity and growth characteristics such as capture of resources; however, the poor establishment of B. napus in 2014 and 2015 is likely responsible for the absence of effects. While B. napus seed was previously considered to be non‐dormant, Soltani et al (2019) provide evidence that disproves this assumption. It is reported that B. napus seed possess both primary and secondary dormancy (Soltani et al, 2019); this helps to explain the poor germination and lack of yield effects observed in 2014 and 2015.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Differences in competitive ability amongst surrogate weeds are expected due to differing growth rates, fecundity and growth characteristics such as capture of resources; however, the poor establishment of B. napus in 2014 and 2015 is likely responsible for the absence of effects. While B. napus seed was previously considered to be non‐dormant, Soltani et al (2019) provide evidence that disproves this assumption. It is reported that B. napus seed possess both primary and secondary dormancy (Soltani et al, 2019); this helps to explain the poor germination and lack of yield effects observed in 2014 and 2015.…”
Section: Discussionmentioning
confidence: 98%
“…While B. napus seed was previously considered to be non‐dormant, Soltani et al (2019) provide evidence that disproves this assumption. It is reported that B. napus seed possess both primary and secondary dormancy (Soltani et al, 2019); this helps to explain the poor germination and lack of yield effects observed in 2014 and 2015. In addition, the future use of B. napus as a surrogate weed is not advisable.…”
Section: Discussionmentioning
confidence: 98%
“…During seed development, ABA is produced in all seed compartments, as suggested by the spatiotemporal expression of its biosynthesis genes [ 22 , 23 ]. ABA synthesized in the endosperm and then transported to the embryo is involved in the induction of seed dormancy [ 22 , 23 , 24 , 25 ]. Likewise, ABA shows an accumulation pattern complementary to the gibberellin (GAs), being the main hormone that inhibits all the processes induced by them [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of light is a key factor involved in the induction of SD. However, it is not yet confirmed whether PD is a requirement to have the ability to acquire SD [ 6 ]. Recently, it was demonstrated that SD is induced in both high- and low-dormancy genotypes and that SD is less responsive to after-ripening (AR) and cold stratification than PD [ 7 ].…”
Section: Introductionmentioning
confidence: 99%